Childhood cancer research in Oxford II: The Childhood Cancer Research Group. Issue 6 (11th September 2018) - Draper, Gerald; Bithell, John; Bunch, Kathryn; Kendall, Gerald; Murphy, Michael; Stiller, Charles
Abstract Background We summarise the work of the Childhood Cancer Research Group, particularly in relation to the UK National Registry of Childhood Tumours (NRCT). Methods The Group was responsible for setting up and maintaining the NRCT. This registry was based on notifications from regional cancer registries, specialist children's tumour registries, paediatric oncologists and clinical trials organisers. For a large sample of cases, data on controls matched by date and place of birth were also collected. Results Significant achievements of the Group include: studies of aetiology and of genetic epidemiology; proposals for, and participation in, international comparative studies of these diseases and on a classification system specifically for childhood cancer; the initial development of, and major contributions to, follow-up studies of the health of long-term survivors; the enhancement of cancer registration records by the addition of clinical data and of birth records. The Group made substantial contributions to the UK government's Committee on Medical Aspects of Radiation in the Environment. Conclusion An important part of the ethos of the Group was to work in collaboration with many other organisations and individuals, both nationally and internationally: many of the Group's achievements described here were the result of such collaborations.